La Représentation du Discours Autre : Principes pour une description - Authier-Revuz, Jacqueline (De Gruyter, 2020)
This book offers a general model of reported speech that relies on clear, well-argued theoretical choices in order to describe accurately the diversity of observed situations. The metalanguage/alterity articulation is critically discussed at various levels (language, discourse, subject) where a central function of differential auto-configuration takes place.
Knowledge Unlatched
French
Keywords: linguistics; Language Arts & Disciplines; Linguistics; General